PELAKSANAAN PEMBAGIAN HARTA WARISAN MENURUT ADAT DI KENAGARIAN AIR TIRIS KABUPATEN KAMPAR - Rahmat Rian Putra; Firdaus '; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Customary law is the original law of the Indonesian nation that comes from unwritten laws of law which grow and develop and is maintained with the consciousness of society because these rules are not written and grow and develop, the customary law has the ability to adjust and elastic. The legal system of inheritance of Islam is the legal system of inheritance which the execution and settlement of the estate when the heir dies. Upon entering the era of reform and post the second amendment of the 1945 Constitution of the State of the Republic of Indonesia hereinafter referred to as the 1945 Constitution of the Republic of Indonesia, the provisions governing customary law are regulated in Article 18B paragraph (2), Inheritance distribution of Kenagarian Water Water of Kampar Regency has many influences of the West Kalimantan Minangkabau customary law especially in terms of division of inheritance, from high inheritance and low inheritance which descends into maternal lineage (Matrilinial). Kenagarian Air Tiris stated that this custom which we believe is very fair especially in the distribution of inheritance that goes down to the women in the family. The distribution of indigenous peoples Kenagarian Air Tiris gives a sense of justice on the part of men is that the justice has been shaped into a customary law special adat law of matrilineal inheritance adhered to the indigenous people of Kenagarian Water Tiris. If they used to be the men of Kenagarian Air Tiris to feel unfair then they would make those changes in the inheritance law that leads to the female lineage.Keywords: Custom, Customary Law, Inheritance Law, Justice